2014
DOI: 10.4103/1673-5374.128250
|View full text |Cite
|
Sign up to set email alerts
|

Local inhibition of GABA affects precedence effect in the inferior colliculus

Abstract: The precedence effect is a prerequisite for faithful sound localization in a complex auditory environment, and is a physiological phenomenon in which the auditory system selectively suppresses the directional information from echoes. Here we investigated how neurons in the inferior colliculus respond to the paired sounds that produce precedence-effect illusions, and whether their firing behavior can be modulated through inhibition with gamma-aminobutyric acid (GABA). We recorded extracellularly from 36 neurons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 60 publications
(121 reference statements)
0
1
0
Order By: Relevance
“…Because the pinna movements have very short latencies (i.e., on the order of 30 ms), it is likely that behaviors associated with the PE occur subcortically. In addition, Wang et al (2014a) showed that enhancing GABA inhibition in the IC can introduce greater suppression to the lagging sound source. Taken together, delayed inhibition in the IC has been proposed as a major neural mechanism for the PE.…”
Section: Discussionmentioning
confidence: 99%
“…Because the pinna movements have very short latencies (i.e., on the order of 30 ms), it is likely that behaviors associated with the PE occur subcortically. In addition, Wang et al (2014a) showed that enhancing GABA inhibition in the IC can introduce greater suppression to the lagging sound source. Taken together, delayed inhibition in the IC has been proposed as a major neural mechanism for the PE.…”
Section: Discussionmentioning
confidence: 99%